Effect of the Empowerment Program on COVID-19 Prevention Practices of Village Health Volunteers - Wongcharoen, Neeranuch; Narin, Rangsiya; Tuanrat, Wilawan (Journal of The Royal Thai Army Nurses, 2022)
This quasi-experimental research, two group pretest–posttest design, aimed to study the effect of the empowerment program on COVID-19 prevention practices of village health volunteers. The participants were fifty persons of village health volunteers who assigned to an experimental group (n = 25) and a control group (n = 25). The research instruments consisted of 1) The empowerment program on COVID-19 prevention practices of village health volunteers for 4-week period 2) Guidebook of knowledge on the COVID-19 prevention practices and 3) COVID-19 prevention practices of village health volunteers’ questionnaire with Cronbach’s alpha coefficient was 0.89. Data were analyzed descriptive statistics and pair t-test and independent t-test. The results revealed that the experimental group had the mean scores on COVID-19 prevention practices of village health volunteers at a highest level ( = 4.59, SD = 0.27) higher than before receiving the empowerment program at a high level ( = 3.53, SD = 0.17) and higher than the control group at a high level ( = 3.55, SD = 0.29) with statistical significance (p<0.001). Research findings can be used as a guideline to promote community nurses and health care teams to reinforce the empowerment of village health volunteers to provide effective and efficiency in COVID-19 prevention practices. They can also be used to prevent the infection of oneself and the community.